Latent and actual entrepreneurship in Europe and the US: some recent developments - A. Roy Thurik; Isabel Grilo (Max Planck Institute of Economics, 2005)
This paper uses 2004 survey data from the 15 old EU member states and the US to explain country differences in latent and actual entrepreneurship. Other than demographic variables such as gender, age and education, the set of covariates includes the perception by respondents of administrative complexities, of availability of financial support and of risk tolerance as well as country-specific effects. A comparison is made with results using a similar survey in 2000. While a majority of the surveyed population identifies lack of financial support as an obstacle to starting a new business, the role of this variable in both latent and actual entrepreneurship appears to be even more counterintuitive in 2004 than in 2000: it has no impact on actual entrepreneurship and is positively related to latent entrepreneurship. Administrative complexities, also perceived as an obstacle by a large majority of the population, have the expected negative impact both for latent and actual entrepreneurship in both years. Country-specific effects are important both for latent and actual entrepreneurship and the comparison of 2000 and 2004 results suggests that, once all other factors are controlled for, an improvement in actual entrepreneurship in the EU relative to the US has taken place in the last four years. However, in terms of unweighted averages actual entrepreneurship remained about the same. Latent entrepreneurship dropped while this drop seems to have occurred evenly in the US and the EU member states.
Keywords: R12; J23; H10; M13; 330; latent entrepreneurship; nascent entrepreneurship; determinatns of entrepreneurship; Europe; Unternehmer; Unternehmensgründung; Schätzung; EU-Staaten; USA